"I have a bone stuck in my throat". Issue 6442 (18th August 1984) - Kirkham, N; English, R
Abstract : Any patient claiming to have swallowed a bone and to have it stuck in his throat should be believed. The bone will probably not show in a lateral radiograph of the neck. The bone must be looked for and removed: otherwise the patient may die of septic complications.